A Single Phase Grid Connected PV System working in Different Modes - Gotekar, P. S.; Muley, S. P.; Kothari, D. P. (Engineering, Technology & Applied Science Research, 2020)
The current grid standards for the single-phase residential PV system expect it to operate at Maximum Power Point Tracking (MPPT) mode under normal operating conditions and to maintain the voltage profile whenever a grid fault occurs. The proposed system supplies power to the load under stable conditions and the PV system works in MPPT mode. When the fault occurs at the Point of Common Coupling (PCC) and the voltage is reduced, the proposed controller maintains the voltage profile by injecting the current fed by the current controller at the PCC. The controller shifts from MPPT to the faulty mode and maintains voltage as per grid requirements. During islanding conditions, the PV system successfully caters to the requirements of the load by shifting the control from MPPT to islanding mode. When the PV system is in operation the power quality is enhanced